2016
DOI: 10.1038/srep36940
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of brown carbon from biomass burning on surface UV and ozone photochemistry in the Amazon Basin

Abstract: The spectral dependence of light absorption by atmospheric particulate matter has major implications for air quality and climate forcing, but remains uncertain especially in tropical areas with extensive biomass burning. In the September-October 2007 biomass-burning season in Santa Cruz, Bolivia, we studied light absorbing (chromophoric) organic or “brown” carbon (BrC) with surface and space-based remote sensing. We found that BrC has negligible absorption at visible wavelengths, but significant absorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 60 publications
4
105
0
Order By: Relevance
“…These retrievals were compared to AERONET SSA at 440 nm and a root mean square error of 0.03 was found (Jethva et al, 2014). MFRSR UV SSA retrievals of carbonaceous aerosols have also been carried out in the Amazon basin (Mok et al, 2016). They reported that brown carbon shows negligible absorption at VIS wavelengths, but significant absorption and strong spectral dependence at UV wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…These retrievals were compared to AERONET SSA at 440 nm and a root mean square error of 0.03 was found (Jethva et al, 2014). MFRSR UV SSA retrievals of carbonaceous aerosols have also been carried out in the Amazon basin (Mok et al, 2016). They reported that brown carbon shows negligible absorption at VIS wavelengths, but significant absorption and strong spectral dependence at UV wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…This may limit the applicability of the Hess et al () refractive indices for the OC component in fire emissions. However, measurements show that the imaginary part of the refractive index in smoke is relatively constant for wavelengths longer than 440 nm (Mok et al, ), which yields relatively small deviations from the BC‐predicted spectral slope of SSA at midvisible and near‐infrared wavelengths (Liu et al, ). Since the radiative transfer calculations are performed for the shortest polarized wavelength of AirMSPI, 470 nm, we argue that the presence of BrC in the smoke plume will likely only have a minimal impact on our results.…”
Section: Methodology and Optical Modelingmentioning
confidence: 99%
“…In the algorithm, a LUT for each aerosol type was calculated assuming a wavelength dependence of aerosol absorptivity based on the literature. Kirchstetter et al [39] obtained the spectral variation of the imaginary refractive index for biomass smoke samples and Mok et al [50] measured the spectral dependence of brown carbon absorptivity in the Amazon. However, the database cannot accurately represent the AOPs of anthropogenic aerosol over Asia.…”
Section: Comparison With Aeronet Aod and Ssamentioning
confidence: 99%